CSIG-29. TRIBBLES-1 (TRIB1) INCREASES TUMOR FORMATION IN AN ORTHOTOPIC MOUSE MODELS BY PROMOTING SURVIVAL OF GBM CELLS AND TREATMENT RESISTANCE. (12th November 2021) - Singh, Karnika; Han, Chunhua; Fleming, Jessica; McElroy, Joseph; Kumar, Ashok; Sebastian, Ebin; Bell, Erica; Robe, Pierre; Haque, Jahar; Chakravarti, Arnab
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most aggressive CNS tumor with an average survival of about 15 months after diagnosis. The current gold standard therapy comprises radiation therapy (RT) and concurrent and adjuvant temozolamide (TMZ). Due to poor prognosis, novel therapeutic targets need to be identified for drug development. To this end, we identified TRIB1 through correlative studies using patient derived methylation data from an institutional cohort as a novel therapeutic target. TRIB1 is a Ser/Thr pseudokinase that functions as a scaffold for the degradation of its substrates and activates Akt and MEK oncogenic pathways. In this study, we show that TRIB1 promoted GBM progression by upregulating survival pathways and reducing RT/TMZ-induced cell death. MATERIALS AND METHODS: In vitro functional validation was performed by overexpression and knockdown approaches. GBM patient derived (PDX) cell lines overexpressing the TRIB1 transgene were used to create an orthotopic tumor model for in vivo studies. Mice were monitored for changes in tumor volume and overall survival. Stable cell lines were generated by puromycin selection. Western blotting was utilized to detect protein levels. RESULTS: Mice inoculated with PDX cells overexpressing TRIB1 transgene had increased tumor volume and worse overall survival compared to the empty vector control. We also observed that TRIB1 overexpression caused decreased apoptosis of PDX cell lines after RT/TMZ treatment. Additionally, an increase in the phosphorylation of ERK and Akt was also noted after TRIB1 overexpression. Consistent with these observations, TRIB1 knockdown sensitized the cells towards radiation and caused decreased Akt phosphorylation/activation as well. CONCLUSION: TRIB1 overexpression decreases overall survival of xenograft bearing mice and promotes GBM cell survival by upregulating survival signaling pathways. This compromises the effects of RT/TMZ therapy, which is reversed after TRIB1 knockdown. Targeting of TRIB1 may reduce oncogenic signaling in GBM cells and therefore would sensitize them towards RT/TMZ therapy.